Low uptake of seasonal influenza vaccination in Al-Jouf region of Saudi Arabia - Ali M. Alzahrani; Holly C. Felix; Nashmi S. Al-Etesh (Elsevier, 2023)
Introduction: Seasonal influenza is a contagious viral respiratory condition typically occurring in the fall to early spring months of the year globally. The risk of infection from seasonal influenza can be greatly reduced with vaccination. Unfortunately, research has indicated that the seasonal influenza vaccination rate in Saudi Arabia is low. This study assessed the uptake of seasonal influenza vaccination among adults residing in Al-Jouf region, Saudi Arabia. Materials and Methods: A cross-sectional survey targeting adults (20-80 years) residing in Al-Jouf region, Saudi Arabia, was conducted to gather information about their sociodemographic characteristics, chronic conditions, knowledge about periodic health examinations (PHE), regular use of PHE, and uptake of seasonal influenza vaccination. Comparative statistics and a multivariate logistic regression analysis were conducted to determine characteristics associated with the uptake of seasonal influenza vaccination. Results: A total of 624 respondents completed the survey and participated in this study. Among the participants, 27.4% indicated they visited their primary healthcare centers or hospitals every year to get a seasonal influenza vaccination. The regression analysis showed that the odds of getting a seasonal influenza vaccination were higher among employed respondents (Odds Ratio [OR] = 1.73; P = 0.039), respondents who were employees of the healthcare sector (OR = 2.31; P = 0.001), and those with a higher PHE Knowledge Score (OR = 1.22; P = 0.008), compared to their counterparts. Conclusions: Seasonal influenza is a serious condition warranting appropriate prevention measures, including vaccination. However, this study confirmed low rates of seasonal influenza vaccination in Al-Jouf Region of Saudi Arabia. Interventions to boost vaccination uptake, in particular among unemployed individuals, those not working in the healthcare sector, and those with lower PHE knowledge Scores, are therefore recommended.